The Impact Of Hepatitis B Knowledge and Stigma on Screening in Canadian Chinese Persons. (2012) - Li, Dorothy; Tang, Taryn; Patterson, Matt; Ho, Michael; Heathcote, Jenny; Shah, Hemant
Abstract : BACKGROUND: Chronic hepatitis B (CHB) infection is endemic in East Asia, and those who emigrate to North America have higher rates of CHB infection when compared with the general population. To date, Chinese persons residing in Canada have not been mandated to be screened for CHB infection. OBJECTIVE: To understand factors that influence hepatitis B screening behaviour among the Chinese community in Toronto, Ontario, and to determine whether stigma acts as a barrier to screening. METHODS: Self-identified Chinese individuals at a family physician's office and at English as a second language (ESL) classes in Toronto completed a questionnaire with demographic questions, a hepatitis B virus (HBV) stigma scale and an HBV knowledge scale. Pearson product moment correlation and multiple regression techniques were used to analyze the data. RESULTS: The study group included 343 individuals. Their mean (± SD) age was 48.76±17.49 years and the majority were born in China (n=229 [68%]). The mean score on the HBV knowledge scale was 10.13±1.76 (range 0 to 15), with higher scores indicating greater HBV knowledge. The mean score on the stigma scale was 54.60±14.18 (range 20 to 100), with higher scores indicating more stigma. Being an immigrant, having a family physician and having greater knowledge of HBV were associated with increased rates of screening for this infection. In contrast, greater levels of HBV stigma were associated with decreased likelihood of screening for HBV infection. CONCLUSIONS: HBV stigma is associated with reduced rates of screening for this infection.